2008
DOI: 10.1007/s00192-007-0541-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in morphology and contractility of the bulbospongiosus and pubococcygeus muscles in nulliparous and multiparous rabbits

Abstract: In women, birth trauma can result in altered anatomy of supporting structures of the pelvic floor and in the development of urinary incontinence. The goal of this study was to investigate the association between parturition and the morphology and function of perineal and pelvic muscles in the female rabbit. In ten nulliparous and ten multiparous same-age females, we investigated morphological, histological (n = 5 females/group), and contractile characteristics (n = 5 females/group) of the perineal bulbospongio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 25 publications
(34 reference statements)
5
33
0
Order By: Relevance
“…We found a significant reduction in the percentage of fast type fibers in the Pc muscle accompanied with an increase in the percentage of intermediate fibers. This is supported by the observations reported by Fajardo and collaborators (2008), which found a significative reduction in the contractile force developed by the Pc muscle during a single twitch or tetanus . The proper contractile function of the Pc muscle and activation during the micturition process could require a relative proportion of a particular type of muscle fibers with predominance of oxidative metabolism, which changes after multiparity.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We found a significant reduction in the percentage of fast type fibers in the Pc muscle accompanied with an increase in the percentage of intermediate fibers. This is supported by the observations reported by Fajardo and collaborators (2008), which found a significative reduction in the contractile force developed by the Pc muscle during a single twitch or tetanus . The proper contractile function of the Pc muscle and activation during the micturition process could require a relative proportion of a particular type of muscle fibers with predominance of oxidative metabolism, which changes after multiparity.…”
Section: Discussionsupporting
confidence: 77%
“…Our results may indicate that the percentages of fast, intermediate, and slow fibers in Bs and Pc muscles of multiparous rabbits are different than those determined in nulliparous female rabbits. Such a finding matches with alterations in morphometry, single twitch contractile force, and the pattern of muscle activation during micturition in female rabbits …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, large motoneurons innervating the Bcm could be responsible for the short duration response of the muscle. Moreover, in agreement with the finding that this muscle has only a small proportion of small-diameter motoneurons, it has been reported that the Bcm in female rabbits has only 9% of type I fibers (Fajardo et al, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…In the female rabbit, the morphology of pelvic and perineal muscles is different (Fajardo et al, 2008). The Pcm is heavier and longer than the Bsm.…”
Section: Pelvic and Perineal Muscles In Virgin And Multiparous Rabbitsmentioning
confidence: 98%